Entrepreneurial Marketing Strategies for Small Businesses : An Exploratory Study of Start-up Companies in India - Sharma, Sarika; Goyal, D. P. (Indian Journal of Marketing, 2020)
Marketing is an important activity for the survival and growth of start-ups, but a start-up – usually with limited budget, moderate capital, and with no concrete customer base – finds it difficult to compete against the industry giants and big players. They can achieve this by converting their weakness into strengths as they can be more flexible in marketing strategies than their competitors in the market. The purpose of this paper was to explore the marketing strategies of start-up companies in India with reference to entrepreneurial marketing. The research is based on a sample of 67 start-up companies operating in India using the mixed research method. Data collection were done using a semi-structured questionnaire comprising of quantitative and open-ended questions. Data were analyzed using SPSS 22.0 and AQUAD 7.0. The findings indicated that start - up companies see marketing as a vital function for their growth and sustainability. Companies are ready to adopt entrepreneurial marketing, and they were already using few of the entrepreneurial marketing techniques. We explored the marketing environment of start-ups in its extant form. The entrepreneurial practitioners as well as the owners of start-up companies may note that this research provides meaningful insights into the significance of their marketing-related activities. The study offers three distinct contributions pertaining to the marketing practices in start-ups : (a) Identifies the research gap within the existing research literature ; (b) explains the marketing strategies by start-up companies ; (c) compares and maps the marketing strategies with entrepreneurial marketing.